2016
DOI: 10.1016/j.prnil.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity towards prostate diseases

Abstract: Evidence has supported obesity as a risk factor for both benign prostate hyperplasia (BPH) and prostate cancer (PCa). Obesity causes several mechanisms including increased intra-abdominal pressure, altered endocrine status, increased sympathetic nervous activity, increased inflammation process, and oxidative stress, all of which are favorable in the development of BPH. In PCa, there are several different mechanisms, such as decreased serum testosterone, peripheral aromatization of androgens, insulin resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1
5

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 74 publications
6
51
1
5
Order By: Relevance
“…Remarkably, these results are in partial agreement with a previous report showing a role of insulin and IGF1 in the modulation of some of these tumoral parameters , in particular a consistent stimulatory effect of IGF1 and insulin on cell proliferation in several prostate cancer cell lines . Therefore, these results, together with other studies reporting a clear association of the risk of prostate cancer with IGF1 levels, insulin levels and/or insulin resistance , reinforce the importance of these two hormones in the pathophysiology of the PG and suggest their putative utility in the prognosis and/or treatment of prostate cancer. In addition, from a clinical point of view, as metformin, an antidiabetic drug associated with a reduction in PCa risk , has been shown to reduce insulin levels and insulin resistance, the results presented herein could invite to suggest that one of the putative mechanisms that might help to explain the beneficial actions of metformin on PCa development and progression might be the reduction in insulin resistance at the PG level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Remarkably, these results are in partial agreement with a previous report showing a role of insulin and IGF1 in the modulation of some of these tumoral parameters , in particular a consistent stimulatory effect of IGF1 and insulin on cell proliferation in several prostate cancer cell lines . Therefore, these results, together with other studies reporting a clear association of the risk of prostate cancer with IGF1 levels, insulin levels and/or insulin resistance , reinforce the importance of these two hormones in the pathophysiology of the PG and suggest their putative utility in the prognosis and/or treatment of prostate cancer. In addition, from a clinical point of view, as metformin, an antidiabetic drug associated with a reduction in PCa risk , has been shown to reduce insulin levels and insulin resistance, the results presented herein could invite to suggest that one of the putative mechanisms that might help to explain the beneficial actions of metformin on PCa development and progression might be the reduction in insulin resistance at the PG level.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, obesity courses with the dysfunction of key regulatory systems, including GH, insulin and IGF1 axes, which are crucial for the correct development and maintenance of several organs , including the PG. Nonetheless, although obesity‐associated alterations in GH , insulin and IGF1 levels, together with the concomitant insulin resistance , have been shown to impact the function of several metabolic organs, are thought to be involved in the increased obesity‐associated cancer risk and can negatively affect testosterone levels , the actual influence of obesity and the concurrent changes in insulin and IGF1 levels in the physiology of normal and tumoral prostate is still to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A study based on an Iranian population showed that obesity and diabetes were risk factors for BPH, but smoking, physical activity and hypertension were not . Studies have suggested that obesity is a risk factor for BPH . A prospective study reported that a higher BMI results in a lower risk of BPH, in contrast to another prospective study suggesting that central obesity was an independent risk factor for BPH .…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk for prostatic cancer correlates with reduced physical activity [183], high BMI [184,185] and diabetes mellitus [186]; farming has been published as a risk factor (although pesticide use is reported as protective; [187]), and lycopene from tomatoes [181,188], catechins, isoflavons and curcumin [7] are probably protective.…”
Section: Prostate Cancermentioning
confidence: 99%